Measuring self-as-context in Chinese college students: Validity and reliability of the Chinese version of self-as-context scale (C-SACS) - Fang, Shuanghu; Huang, Mingjie; Wang, Yiyi (Frontiers in Psychology, 2022)
Objective: To examine the validity and reliability of the Chinese version of Self-as-Context Scale (SACS) in college students. Method: We used clustered random sampling to recruit 708 Chinese colleges students. All participants completed the SACS and 343 of them were asked to complete the validation questionnaires (Satisfaction with Life Scale, Peace of Mind Scale, Acceptance and Action Questionnaire-II, Mindful Attention Awareness Scale, Cognitive Fusion Questionnaire-Fusion, and Depression Anxiety Stress Scale-21) at the same time. After 3 weeks, 217 participants filled out the SACS again to assess the test-retest reliability. We used the Results: The exploratory factor analysis showed that the SACS consisted of two factors (Centering and Transcending), with a total of 9 items. The confirmatory factor analysis demonstrated that the two-factor structure fit well (=55.40, df=22, CFI=0.977, TLI=0.963, RMSEA=0.065, SRMR=0.032). According to the results of the measurement invariance tests, the configural invariance, metric invariance, scalar invariance, and the strict invariance of the 2-factor model, the C-SACS scores were comparable across genders. Additionally, the C-SACS total score and its subscale scores were significantly positively correlated with positive indicators of mental health (life satisfaction, affective well-being), significantly negatively correlated with negative emotions (depression, anxiety, stress), significantly negatively correlated with experiential avoidance and cognitive fusion (with exception of the Transcending factor), and significantly positively correlated with mindful attention and awareness. The Cronbach’s α coefficients of the C-SACS and two subscales were .88 [.71, .90], .80 [.87, .90] and .85 [.83, .88] and McDonald’s ω = .88 [.87, .90], ω=.80 [.78, .83], ω=.85[.83,.88]. The test-retest reliability (ICC) was .73 and .72, respectively. Conclusion: The results of our study suggest that the Chinese version of SACS has good reliability and validity in Chinese college students.